PENGELOLAAN SUMBER DAYA AIR BAWAH PERMUKAAN DENGAN TEKNOLOGI IMBUHAN BUATAN - Sudinda, Teddy W (Jurnal Air Indonesia, 2014)
Subsurface water resource is a natural resource that is essential for life, and therefore must be preserved so that its presence can be used in a sustainable manner. Subsurface water sources should be managed in an integrated manner based on ground water basin that can be used optimally. For the preservation of groundwater using artificial recharge technology (shallow recharge wells, Deep recharge wells and reservoir recharge). The purpose of this study was to assess the ability of absorption of artificial recharge in the shallow, medium and deep aquifer. Absorption capability will be tested by direct measurements in the field by filling water into shallow recharge wells, deep recharge wells and reservoirs recharge in the catchment area. The more water that can be absorbed by means of artificial recharge capabilities can work well. From the results of research conducted can be seen that each has its own advantages and can be implemented in accordance with the existing field conditions.Ã‚Â Keywords: Subsurface water, aquifer, Permeability, Artificial Feed